The influence of vegetal cover on carbon assimilation by Prochilodus lineatus (Characiformes: Prochilodontidae) in the upper Paraná river floodplain - Serragiotto, Mariana Cristina; Souza Filho, Edvard Elias de; Couto, Edivando Vitor do; Manetta, Gislaine Iachstel; Benedito, Evanilde (Acta Scientiarum. Biological Sciences, 2014)
The present study examined the influence of the availability of riparian vegetation and C3 emergent aquatic macrophytes on carbon assimilation by Prochilodus lineatus. The vegetal cover of these producers, available at 30 m of the bank, for the terrestrial ecosystem of the rivers Baia, Ivinheima and Paraná, was quantified with the image processing Landsat 5 TM, of the year 2000, period of sampling of the biological material at each river. The assimilation of the energy sources (riparian vegetation and C3 aquatic macrophytes, C4 aquatic macrophytes, periphyton, and phytoplankton) by P. lineatus was determined by analysis of stable carbon isotopes (δ13C). The area of vegetal cover was estimated at 1,017 km2 in the Ivinheima river, 669 km2 in the Paraná river, and 268 km2 in the Baia river. The assimilation of the carbon from riparian vegetation and aquatic macrophytes was proportional to the availability in the environment, but these producers were not the main source of carbon for P. lineatus. Thus, in the rivers with greater vegetation cover, consequently, these items had higher availability in the water body becoming an important carbon source for the species maintenance.